2016
DOI: 10.18203/2394-6040.ijcmph20163366
|View full text |Cite
|
Sign up to set email alerts
|

Study of prevalence and risk factors of hypertension in adults in an urban slum area of Western Maharashtra, India

Abstract: INTRODUCTIONHigh blood pressure (BP) is a major public health problem in India and its prevalence is rapidly increasing among both urban and rural populations. 1 In fact, hypertension is the most prevalent chronic disease in India. The prevalence of hypertension ranges from 20-40% in urban adults and 12-17% among rural adults. The number of people with hypertension is projected to increase from 118 million in 2000 to 214 million in 2025, with nearly equal numbers of men and women.2 In India, the trend is incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 4 publications
1
7
1
Order By: Relevance
“…We found that age was the most important risk factor for HTN, consistent with other studies in similar conditions (Bendhari et al, 2016;Ramani & Suresh, 2020;Banerjee et al, 2016;Daniel et al, 2013;Gadallah et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that age was the most important risk factor for HTN, consistent with other studies in similar conditions (Bendhari et al, 2016;Ramani & Suresh, 2020;Banerjee et al, 2016;Daniel et al, 2013;Gadallah et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…The overall prevalence of HTN in this study (25.7%) is higher than that of similar populations in Maharashtra (15.15%) and Bangalore city (21.5%) in India (Bendhari et al, 2016;Ramani & Suresh, 2020). However, the prevalence is considerably lower than that of the population from Kolkata, India (42%), Lagos, Nigeria (38.2%), and Cairo, Egypt (31.2%) (Banerjee et al, 2016;Daniel et al, 2013;Gadallah et al, 2018).…”
Section: Discussioncontrasting
confidence: 46%
“…To estimate the sample size, we considered that the prevalence of HTN among Maharashtra slum population was 15.15% reported by Bendhari et al [6].…”
Section: Methodsmentioning
confidence: 99%
“…14 Studies carried out in slums have also reported the prevalence of hypertension as high as 14 to 26%. [15][16][17] In view of the above facts, the present study has been carried out to determine the prevalence of hypertension and factors associated with it in urban slums of Rajamahendravaram, Andhra Pradesh.…”
Section: Introductionmentioning
confidence: 99%